2018
DOI: 10.3389/fphar.2018.01167
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profiling and Comparison of Sangju Ganmao Tablet and Its Component Herbs Using Two-Dimensional Liquid Chromatography to Explore Compatibility Mechanism of Herbs

Abstract: Sangju Ganmao tablet (SGT), a well-known Chinese patent medicine used to treat cold symptoms, is made from eight herbal medicines. In this study, an off-line hydrophilic interaction × reversed-phase two-dimensional liquid chromatography (HILIC × RP 2D-LC) method was developed to comprehensively separate the chemical constituents of SGT. Through optimization of the experimental conditions, a total of 465 peaks were finally detected in SGT, and the structures of 54 selected compounds were fully identified or ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…These results showed that the application of first-order chromatographic fingerprinting has limitations. Ji et al compared the profiles of compounds in traditional Chinese medicine (TCM) tablets and their herbal components using 2D-LC-quadrupole-TOF (q-TOF) MS ( Ji et al, 2018 ). Fifty-four compounds were identified from the total 465 peaks found in the tablet samples.…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…These results showed that the application of first-order chromatographic fingerprinting has limitations. Ji et al compared the profiles of compounds in traditional Chinese medicine (TCM) tablets and their herbal components using 2D-LC-quadrupole-TOF (q-TOF) MS ( Ji et al, 2018 ). Fifty-four compounds were identified from the total 465 peaks found in the tablet samples.…”
Section: Applications Of Fingerprinting Methodsmentioning
confidence: 99%
“…Water, water-methanol (1:1, v/v), and methanol were selected as the reference extraction solvent, and then the extraction procedures were repeated under the same conditions as DESs. All the extract solutions were filtered through a 0.45 µm membrane before HPLC analysis [25]. Three parallel experiments were performed.…”
Section: Coumarins Extraction From Cortex Fraxini By Deep Eutectic Somentioning
confidence: 99%
“…However, it exhibits slightly inferior effectiveness in relieving cough and resolving phlegm. 16 Therefore, drugs such as Baibu, Baiqian, and Aster are frequently added to strengthen the therapeutic effects of Sangju-Yin. Sangju cough mixture comprises Sangju-Yin plus Baiqian, Fritillaria thunbergii, Xanthium sibiricum, Scutellaria baicalensis , reed root, mulberry leaves, and chrysanthemum, which disperse wind-heat and relieve cough; almonds, Cynanchum glaucescens , and Platycodon grandiflorum , which lower lung qi and relieve cough; Fritillaria thunbergii and Scutellaria baicalensis , which disperse lung heat; and Forsythia suspensa and reed root, with heat-clearing, detoxifying, and thirst-quenching properties.…”
Section: Introductionmentioning
confidence: 99%